A survey for hydroxyl in the THOR pilot region around W43 - Walsh, Andrew; Beuther, H.; Bihr, S.; Johnston, K.; Dawson, J.; Ott, J.; Longmore, S.; Luong, Q.; Klessen, R.; Ragan, S.; McClure-Griffiths, N.; Brunthaler, A.; et al. (Oxford University Press, 2015)
We report on observations of the hydroxyl radical (OH) within The Hι, OH, Recombination line survey (THOR) pilot region. The region is bounded approximately between Galactic coordinates l = 29 .2 to 31 .5 and b = −1 .0 to +1 .0 and includes the high-mass star-forming region W43. We identify 103 maser sites, including 72 with 1612 MHz masers, 42 showing masers in either of the main-line transitions at 1665 and 1667 MHz and four showing 1720 MHz masers. Most maser sites with either main-line or 1720 MHz emission are associated with star formation, whereas most of the 1612 MHz masers are associated with evolved stars. We find that nearly all of the main-line maser sites are co-spatial with an infrared source, detected by GLIMPSE. We also find diffuse OH emission, as well as OH in absorption towards selected unresolved or partially resolved sites. Extended OH absorption is found towards the well-known star-forming complex W43 Main.